EFEKTIVITAS MEDIA PERMAINAN LUDO BERBASIS CHEMOEDUTAIMENT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PERIODIK UNSUR KELAS X SMAN 5 PADANG TAHUN PELAJARAN 2018/2019 - Farly Yanida, Iswendi (Menara Ilmu, 2018)
This study based on the availability of an instructional media based on chemo edutainment inform of ludo game which it’s effectivity toward student’s study result haven’t tested yet. Thisstudy aims to reveal the effectivity of the usage of an instructional media based on chemoedutainment in form of ludo game for element periodic system toward 10th student’s study resultfrom SMAN 5 Padang.The type of this research was quasi-experimental with non-equivalent control group design. Thepopulation for this research was 10th grade science student from SMAN 5 Padang. The samplewas chosen by using purposive sampling technique which resulted that X MIPA 5 chosen asexperiment class and X MIPA 4 as control class. The data analysis technique was t-test todetermine the difference of student’s study result and N-Gain test to determine the increase ofstudent’s understanding.The result of this research showed there are difference between study result from experimentclass and control class. This is proven by the average point of the posttest from experiment classand control class which is 85,67 and 79,89 respectively. This result also supported by t-testanalysis which showed tcount(2,84) > ttable(1,67) on significant standard α= 0,05 with dk= 70and probality t0,95. The increase of better student’s understanding also happened in experimentclass compared to control class. This fact proven with the average of N-Gain test point fromexperiment class 0,76 which considered as high and control class 0,63 which considered asmedium.Keywords : effectivity, instructional media ludo, chemo edutainment, element periodic system, studyresult